LLTD: Link Layer Topology Discovery Protocol. A Windows® Rally„¢ Specification. - Ward, Glenn; Tan, Alvin; Gavrilescu, Alexandru; Black, Richard; Donnelly, Austin (2006)
This specification describes how the Link Layer Topology Discovery (LLTD) protocol operates over wired (802.3 Ethernet) and wireless (802.11) media. As the protocol name suggests, the core functions of LLTD enable applications to discover the topology of a network. In addition, LLTD has optional QoS Extensions that applications can use to diagnose problems, especially those involving signal strength on wireless networks or bandwidth constraints in home networks. LLTD is a key component of the Microsoft® Windows® Rally™ set of technologies.